US patent no. 7,107,176 B2: Sensor fusion using self evaluating process sensors - Henry, M; Duta, M (United States Patent and Trademark Office, 2006)
A measurement processing system is disclosed for fusing measurement data from a set of independent self-validating (SEVA™) process sensors monitoring the same real-time measurand in order to generate a combined best estimate for the value, uncertainty and measurement status of the measurand. The system also provides consistency checking between the measurements. The measurement processing system includes a first process sensor and a second process sensor. Each of the first and second process sensors receive a measurement signal from a transducer and generate independent process metrics. A measurement fusion block is connected to the first and second process sensors, the measurement fusion block is operable to receive the independent process metrics and execute a measurement analysis process to analyze the independent process metrics and generate the combined best estimate of the independent process metrics.